New Virus Targets a Development Environment. - Paulson, Linda Dailey (Computer (00189162), 2010)
The article focuses on a virus which threatens to infect a development environment. It states that the virus, referred to as Induc by Kaspersky Antivirus, affects the Delphi software development environment versions 4 to 8 and could allow legitimate software to contain unwanted codes and cause antivirus products to stop working. The article discusses that the virus has been found in two free tools in the internet. According to the article, vendors have blocked the virus but a reinstallation of the Delphi is essential to the elimination of the virus.